Pengaruh Achievement Goal Orientation Terhadap Prokrastinasi Pada Mahasiswa Keperawatan Di Stikes Piala Sakti Pariaman - Rezki Yeti Yusra; Aminah Aminah; Rika Astria Rishel (Nan Tongga Health And Nursing, 2025)
Procrastination can be carried out by students from various scientific fields, including nursing students. Procrastination is the behavior of delaying completing tasks. Students who have achievement goal orientation can avoid procrastination behavior. Individuals who have strategies to achieve their goals in achievement can indirectly manage their time effectively, so they will prevent procrastination behavior in carrying out tasks or procrastination in completing tasks. This research aimed to determine whether achievement goal orientation influences procrastination in undergraduate nursing students. This research used a quantitative approach with simple linear regression model data analysis techniques. A total of 143 undergraduate nursing students participated in this study. The category of achievement goal orientation was identified: low 30 (21%), medium 87 (60.8%), and high category 26 (18,2%). Meanwhile, the results of the procrastination category were: low 15 (10,5%), medium 101 (70.6%), and high 27 (18,9%). The coefficient of determination test showed that the influence of achievement goal orientation on procrastination was 0,367. The hypothesis test result of the significance score is 0.000, which means the score is sig. 0.000 ˂ 0.05, so it can be stated that there is a significant influence between achievement goal orientation and procrastination in nursing students. This result of the beta coefficient was -1.283which means a negative direction where if achievement goal orientation increases by 1 point, then procrastination will decrease by 1.283 points. This study showed there is an influence of achievement goal orientation on procrastination in nursing students, where the achievement goal orientation variable is higher, then the value of the procrastination variable will be lower. Achievement goal orientation only influences 36.7% of procrastination; other factors such as self-management, self-efficacy, and environmental conditions, also play an important role. Therefore, efforts to overcome procrastination should focus on strengthening students' personal motivation and goals.